Qualitative validation of a financially affordable Islamic home financing model - Mohd Zaidi Md Zabri; Omar Mohammed Mustafa (ISRA International Journal of Islamic Finance, 2018)
Purpose: This study aims to validate a potential synergistic venture between cash waqf (Islamic endowment) institutions (CWIs) and financial cooperatives (FCs) in the provision of affordable Islamic home financing (IHF) in Malaysia. Design/methodology/approach The study adopted semi-structured interviews with ten experts to validate the cash waqf-financial-cooperative-mushārakah mutanāqiṣah (CWFCMM) model. Thematic analysis technique was used to analyse the verbatim texts. Findings The findings show that the majority of the informants have positive perceptions of the potential of the CWFCMM model to provide financially affordable IHF products in Malaysia. Nevertheless, this study sheds light on the varying degrees of latent issues and challenges that might arise in the implementation of this model. For example, FCs need to practice the correct business model, implement good governance structures and employ the right people. Meanwhile, CWIs need to work on their accountability issues by publishing their audited accounts in mainstream newspapers, much like what is being done by non-governmental organisations such as the widely recognised Malaysian Medical Relief Society (MERCY Malaysia). Research limitations/implications This study interviewed a small, industry-specific number of informants in generating its findings. Time and budget constraints are some of the limiting factors in carrying out the study. Because of these factors, the generalisation of the study's findings will be limited. Practical implications First, the CWFCMM model offers an alternative, financially affordable IHF instrument to low- and middle-income households in Malaysia. Second, the involvement of third-sector institutions such as FCs and CWIs in the provision of IHF will reduce the burden of the government in its spending on home financing solutions for civil servants. Third, this model will harness the potential of waqf-based financing beyond the contemporary limited applications to mosques, graveyards and taḥfīẓ (Qurʾan memorization) schools. Originality/value This study presents an alternative IHF model that transcends the current institutional framework that is heavily dominated by Islamic commercial banks and government-owned home financing institutions. The study does not focus on a single third-sector institution but on an integration of at least two of them, CWIs and FCs, in implementing the IHF model.
Keywords: 330; Cash waqf; Financial cooperatives; Islamic banking; Islamic home financing; Mushārakah Mutanāqiṣah; Waqf